Missionary conspiracy : letters to a postmodern Hindu - Mangalwadi, Vishal; Shourie, Arun. (Mussoorie : Nivedit Good Books, 1996)
Letters written to Arun Shourie on the role of Christian missions in India; covers the past 200 years.
Includes bibliographical references and index.
Keywords: Missions -- India; Hinduism; India -- Religion